(untitled) (Journal of Academic Research, 2023)
Salmonella and Shigella is one of the most important foodborne pathogens worldwide; This study was aimed to investigate the presence of pathogenic Salmonella and Shigella isolated from eggs; then screening isolates for stn gene in Salmonella and invC gene in Shigella using PCR technique. A total of 50 samples of distributed eggs were randomly collected from stores, supermarkets and street vendors around the city. Two Salmonella isolates were found in egg samples 4% (2/50) and one Shigella was found in egg sample 2% (1/50). All Salmonella isolates were positive for the stn gene and Shigella was positive for the invC gene. The result confirmed that the transfer of these organisms through the food chain poses imminent danger to the consumer and concluded that there is a need for continuous surveillance of eggs especially the locally produced ones, suggested using PCR to minimize the possibility of human infections with Salmonella and Shigella.